Machine learning approaches to predict and detect early-onset of digital dermatitis in dairy cows using sensor data - Magana, Jennifer; Gavojdian, Dinu; Menahem, Yakir; Lazebnik, Teddy; Zamansky, Anna; Adams-Progar, Amber (Frontiers in Veterinary Science, 2023)
The aim of this study was to employ machine learning algorithms based on sensor behavior data for (1) early-onset detection of digital dermatitis (DD); and (2) DD prediction in dairy cows. Our machine learning model, which was based on the Tree-Based Pipeline Optimization Tool (TPOT) automatic machine learning method, for DD detection on day 0 of the appearance of the clinical signs has reached an accuracy of 79% on the test set, while the model for prediction of DD 2 days prior to the appearance of the first clinical signs, which was a combination of K-means and TPOT, has reached an accuracy of 64%. The proposed machine learning models have the potential to help achieve a real-time automated tool for monitoring and diagnostic of DD in lactating dairy cows, based on sensor data in conventional dairy barns environments. Our results suggest that alterations in behavioral patterns can be used as inputs in an early warning system for herd management in order to detect variances in health and wellbeing of individual cows.